2011
DOI: 10.1007/s10648-011-9173-8
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Understanding of Movements in Dynamic Visualizations: an Embodied Perspective

Abstract: Learners studying mechanical or technical processes via dynamic visualizations often fail to build an accurate mental representation of the system's movements. Based on embodied theories of cognition assuming that action, perception, and cognition are closely intertwined, this paper proposes that the learning effectiveness of dynamic visualizations could be enhanced by grounding the movements of the presentation in people's own bodily experiences during learning. We discuss recent research on embodied cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 101 publications
(121 reference statements)
1
77
1
4
Order By: Relevance
“…Thus, we can only conclude that self-gesturing by 'moving along with an arrow' does not seem to benefit learning from animations. Perhaps using other kinds of self-performed gestures or other strategies to ground information might be more effective to foster learning from non-human dynamic systems via animation (De Koning & Tabbers, 2011). In the Glenberg et al (2004) study, for example, participants first read story sentences and then moved objects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we can only conclude that self-gesturing by 'moving along with an arrow' does not seem to benefit learning from animations. Perhaps using other kinds of self-performed gestures or other strategies to ground information might be more effective to foster learning from non-human dynamic systems via animation (De Koning & Tabbers, 2011). In the Glenberg et al (2004) study, for example, participants first read story sentences and then moved objects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As animations provide a direct depiction of these movements, the main challenge is to translate perception of these movements to the construction of a runnable mental representation. Adding gestures that are aligned to the perceived movements might help in constructing such a mental model and thus foster learning from the dynamic visualization (De Koning & Tabbers, 2011).…”
Section: Gestures Facilitate Learningmentioning
confidence: 99%
“…Success in such tasks requires a learner to have a precise mental model of the continuity of changes underlying the movements, which may be more easily conveyed by dynamic visualization. Particularly, tasks that involve understanding and recalling biological motion may be more easily conveyed by using dynamic visualizations (De Koning & Tabbers, 2011;Van Gog, Paas, Marcus, Ayres, & Sweller, 2009). Accordingly, one may argue that dynamic visualizations are well suited for learning locomotion patterns, because they allow learners to acquire the necessary mental model by showing the dynamics explicitly.…”
Section: Presentation Formats Of Visualizationsmentioning
confidence: 99%
“…There has been interest in the impact of different forms of physical activity during instruction and cognition (Barsalou, 2008; Koning & Tabbers, 2011), and some research has suggested that action during periods of learning may aid in knowledge acquisition. Cook, Mitchell, and Goldin-Meadow (2008), for example, showed that hand gestures made by children while learning about mathematics improved retention of the learned concepts.…”
Section: Introductionmentioning
confidence: 99%